2001
DOI: 10.1016/s0304-3959(00)00397-3
|View full text |Cite
|
Sign up to set email alerts
|

Mu- and delta-opioid receptors are downregulated in the largest diameter primary sensory neurons during postnatal development in rats

Abstract: The aim of this study was to investigate the postnatal development of mu-(MOR) and delta-opioid receptor (DOR) immunoreactivity in rat dorsal root ganglia. Lumbar dorsal root ganglia (DRG) from postnatal day (P) 0, 3, 7 and 21 rat pups were immunostained for MOR and DOR. Proportions of MOR +ve and DOR +ve cells were calculated from profile counts. Diameters of MOR +ve and DOR +ve cells were measured and compared to -ve cells. The coexpression of MOR and neurofilament (NF200) in DRG over this postnatal period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 32 publications
5
49
1
Order By: Relevance
“…Furthermore, long-term exposure to proinflammatory chemokines compromises the function of MORs on sensory neurons of dorsal root ganglia. MORs are preferentially expressed on small to medium diameter neurons (32). Our data from immunohistochemical staining clearly showed that CCR1 and -opioid receptors were coexpressed on the same neuronal cells.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, long-term exposure to proinflammatory chemokines compromises the function of MORs on sensory neurons of dorsal root ganglia. MORs are preferentially expressed on small to medium diameter neurons (32). Our data from immunohistochemical staining clearly showed that CCR1 and -opioid receptors were coexpressed on the same neuronal cells.…”
Section: Discussionsupporting
confidence: 49%
“…However, in mouse DRG neurons, ␦-receptors are the first to be expressed on embryonic day 12.5 (E12.5), followed by the -(E13.5) and -receptors (E17.5) (Zhu et al, 1998). In rat, a greater proportion of DRG neurons expressing -and ␦-receptors was found before postnatal day 7 (P7) than at P21 (-receptor was not examined) (Beland and Fitzgerald, 2001;Nandi et al, 2004). During the first postnatal week, both opioid receptors were detected in cells of all sizes, but by P21, expression was restricted to small-and medium-diameter cells, suggesting a selective down-regulation in nonnociceptive neurons (Beland and Fitzgerald, 2001;Nandi et al, 2004).…”
Section: Plasticity and Regulation Of Peripheral Opioid Receptorsmentioning
confidence: 99%
“…In rat, a greater proportion of DRG neurons expressing -and ␦-receptors was found before postnatal day 7 (P7) than at P21 (-receptor was not examined) (Beland and Fitzgerald, 2001;Nandi et al, 2004). During the first postnatal week, both opioid receptors were detected in cells of all sizes, but by P21, expression was restricted to small-and medium-diameter cells, suggesting a selective down-regulation in nonnociceptive neurons (Beland and Fitzgerald, 2001;Nandi et al, 2004). This notion was supported by another study examining -receptor mRNA and function (Wu et al, 2009).…”
Section: Plasticity and Regulation Of Peripheral Opioid Receptorsmentioning
confidence: 99%
“…We have addressed these questions by focusing on the murine and ␦ opioid receptors (MOR and DOR, respectively), homologous G protein-coupled neuropeptide receptors that are natively co-expressed in several cell types (18 -20) yet differ significantly in membrane trafficking properties (21)(22)(23). Studies of cultured cells indicate that both MOR and DOR are rapidly endocytosed via clathrin-coated pits and colocalize in early endosomes within several minutes after agonist-induced activation.…”
mentioning
confidence: 99%